2006
DOI: 10.1038/sj.jid.5700013
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavonoid Photoprotection in Mouse and Human Skin Is Dependent on Metallothionein

Abstract: Previous studies report that selected topical isoflavonoids are immunoprotective in both mice and humans, when applied following UV irradiation. Isoflavonoids have documented antioxidant activity, but their mechanism of immunomodulation remains unclear. This study examines whether photoimmunoprotection by the isoflavonoids might result from their interaction with one cutaneous antioxidant known to modulate UV photodamage, metallothionein (MT). In mice bearing a null mutation for MT-I and -II, we found that imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 28 publications
2
21
0
2
Order By: Relevance
“…However, cutaneous MT might have such a role, being a recognized antioxidant and a photoimmune protectant in both mice and humans, as well as a readily inducible factor by topical equol treatment in SSUVirradiated normal-haired mouse skin (9,10). There is now evidence from cultured human tumor cell lines that the MT gene is regulated by the ER (17) and that the zinc-finger domain of the ER is supplied with zinc by MT (18), demonstrating an intimate intracellular relationship between MT and estrogenic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cutaneous MT might have such a role, being a recognized antioxidant and a photoimmune protectant in both mice and humans, as well as a readily inducible factor by topical equol treatment in SSUVirradiated normal-haired mouse skin (9,10). There is now evidence from cultured human tumor cell lines that the MT gene is regulated by the ER (17) and that the zinc-finger domain of the ER is supplied with zinc by MT (18), demonstrating an intimate intracellular relationship between MT and estrogenic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative radical scavenging by equol has been reported in numerous systems (6)(7)(8). Furthermore, both equol and NV-07␣ have the capacity to stimulate the solar-simulated UV radiation (SSUV) induction of metallothionein (MT) in the skin (9). In addition to its capacity for metal ion chelation, MT is one of the endogenous cutaneous antioxidants that have been identified as relevant for protection against oxidative photodamage (10).…”
mentioning
confidence: 99%
“…The response of the skin to overexposure to UV radiation comprises inflammation, observed as the erythema and oedema of the sunburn reaction, the suppression of T-cell-mediated immune function both locally in the irradiated skin and systemically, the increased lipid peroxidation of cell membranes, and the depletion of the endogenous cutaneous antioxidants such as metallothionein, glutathione and the glutathione peroxidases and reductases [1,2,3,4]. Development of oxidative stress then stimulates the induction of a further redox-regulated stress enzyme, haem oxygenase-1, which plays an important protective role against immune suppression [5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, equol has been shown to stimulate the gene expression of the SH-rich detoxifying proteins, like metallothionein-1H and metallothionein-2H, that protect against metal toxicity [85,94]. Finally, Widyarini et al have shown that equol's photo-protective effect in mouse and human skin is dependent on metallothionein [96].…”
Section: Equol Increases Skin Antioxidant Defense and Stimulates Nrf2mentioning
confidence: 99%